Evaluation of the Antioxidant Potential of Calix[4]Pyrrole ,Resorcin[4]Arene, and Pyrogallol[4]Arene Via DPPH Assay: Evaluasi Potensi Antioksidan Calix [4] Pirol, Resorcin [4] Arene, dan Pyrogallol [4] Arene Melalui Uji DPPH - Alhamami , Samer Salem; Alnuaim , Maan; Raheem, Leaqaa Abdulredha (Indonesian Journal on Health Science and Medicine, 2025)
Background: Oxidative stress, caused by an imbalance between free radical production and antioxidant defenses, contributes to various diseases, including cancer, cardiovascular disorders, and neurodegenerative conditions. Antioxidants mitigate these effects by neutralizing free radicals, preventing cellular damage. The DPPH assay is a widely used method for evaluating antioxidant activity, measuring the ability of compounds to reduce the stable DPPH radical and decrease absorbance at 517 nm. Calix[4]pyrrole, Resorcin[4]arene, and Pyrogallol[4]arene derivatives are macrocyclic compounds with structural features that influence their antioxidant properties. objective: This study aims to assess the antioxidant activity of Calix[4]pyrrole derivatives, Resorcin[4]arene derivatives, and Pyrogallol[4]arene derivatives using the DPPH radical scavenging assay to determine their potential for biomedical applications.Material and Methods: The DPPH assay was conducted by preparing a 0.4 mg/mL DPPH solution and measuring the reduction in absorbance at 517 nm after interaction with the tested compounds. The scavenging activity (%) was calculated using the standard equation.Results: : Pyrogallol[4]arene derivative (Cpd5) exhibited the highest antioxidant activity (65.81% ± 0.12), followed by Resorcin[4]arene derivative (Cpd4) with 59.79% ± 0.25. In contrast, Calix[4]pyrrole derivatives displayed lower antioxidant activity, with Cpd1 and Cpd6 showing the least efficiency at 7.38% ± 0.09 and 5.76% ± 0.09, respectively.Conclusion:The findings suggest that the antioxidant activity is significantly influenced by the presence and arrangement of hydroxyl groups. Compounds with a higher number of hydroxyl groups demonstrated superior radical scavenging potential, making them promising candidates for further pharmacological studies. Highlights: Oxidative stress leads to diseases; antioxidants counteract free radicals. Evaluate antioxidant activity of macrocyclic compounds using DPPH assay. Hydroxyl-rich compounds showed highest activity, promising for pharmacological studies. Keywords: DPPH assay, antioxidant activity, Calix[4]pyrrole, Resorcin[4]arene, Pyrogallol[4]arene, free radicals